Pemanfaatan Ekstrak Tulang Ikan Bandeng (Chanos-Chanos) Dalam Pembuatan Opak - Setiawan, Erwin; Yosef Anggoro Wicaksono, Herman (JURNAL PARIWISATA VOKASI, 2024)
This research aims to utilize milkfish bone extract in making opaque as an effort to increase the nutritional value of snack products. The research method used is experimental with a quantitative approach. Data was collected through organoleptic tests involving professional and non-professional panelists. The research results showed that opak containing milkfish bone extract had a better taste and higher nutritional content compared to opak without this extract. It is hoped that this research can become a reference for the food industry in developing healthy and nutritious products.